The deglaciation history of Cape Norton Shaw Inlet (eastern Canadian Arctic Archipelago) - Elodie Bracquart; Jean-Carlos Montero-Serrano; Patrick Lajeunesse; Guillaume St-Onge; Luke Copland; Andrew K Hamilton; Gabriel Joyal (Quaternary Science Reviews, 2026)

Age, growth and sexual dimorphism of the monkeyface prickleback ( Cebidichthys violaceus ) - Kevin D. Hinterman; Matthew R. Hoehn; Luke D. Gardner; Scott L. Hamilton (Journal of Fish Biology, 2026)
Accurate estimates of age, growth and maturation are fundamental to fisheries assessment, conservation and the development of emerging aquaculture species. However, life‐history parameters can vary within species and may be influenced by factors such as sexual dimorphism, which is often poorly quantified in non‐commercial or understudied species. The monkeyface prickleback ( Cebidichthys violaceus ), one of the largest herbivorous fish along the west coast of North America and a potential aquaculture candidate, remains relatively understudied with respect to life‐history variation and sexual dimorphism. This study updates and expands previously reported life‐history parameters of C. violaceus by incorporating a wider size range of individuals, including juveniles, and evaluates sexual dimorphism in cranial morphology using geometric morphometric methods. Von Bertalanffy growth functions based on otolith sectioning and updated length‐weight relationships were developed for adult males, females and all fish combined. Length and age at maturation were estimated to be earlier than previously reported, with most individuals maturing before 28.2 cm in length and 5 years of age. Females were generally heavier than males of the same length, whereas males were longer than females of the same age and attained greater maximum lengths. Condition factor only differed between adult males and juveniles. Sexual dimorphism was assessed using body metrics and quantified through geometric morphometric analyses of head and supraorbital crest shape. Head shape, supraorbital crest shape and eye size differed significantly between sexes, with morphological differences becoming more pronounced with increasing body size, providing clear evidence of sexual dimorphism in adult C. violaceus . These findings will aid in the sustainable management of wild populations and optimise broodstock selection and aquaculture development for the species.

Reproduction and embryonic development of monkeyface prickleback Cebidichthys violaceus in captivity - Kevin D. Hinterman; Matthew R. Hoehn; Luke D. Gardner; Scott L. Hamilton (Journal of Fish Biology, 2026)
Understanding the sequence of embryonic and larval development and the factors necessary to induce reproduction in captivity are critical for developing new species for commercial or conservation aquaculture. In this study, we describe the adult reproductive behaviours and development of eggs, embryos and early larvae of captive monkeyface pricklebacks, Cebidicthys violaceus , compared to previously documented wild observations. Eggs were laid in cohesive clutches and guarded by the male parent until hatching began 23 days post fertilization at 13°C. Fertilized eggs were spherical, approximately 1.5 mm in diameter, covered in an opaque chorion, and contained six adhesive pads around the outside. We characterized the rate of depletion of yolk and the oil globule and growth of the embryo from fertilization until hatching. Notable embryonic stages were documented, including the timing of the first heartbeat, and the development of otoliths, intestinal tract, eye pigmentation, mouth, fins and the circulatory system. Larval length at hatching was about 7.4 mm, and larvae were immediately mobile and feeding on live food. Larvae were cultured and observed up to 18 days post hatch.

Development and pilot testing of AYA-RISE, a risk information and screening education intervention for adolescents and young adults with cancer risk syndromes - Junne Kamihara; Lauren Fisher; Jaclyn Schienda; Rebecca Vanderwall; Moran Snir; Guy Snir; Emilie Simmons; Andrew Khalaj; Evan Goler; Kayla V. Hamilton; Christopher C. Porter; Bojana Pencheva; et al. (Familial Cancer, 2026)

Optimizing bromoform content in Gracilaria parvispora: the role of environmental stressors - Steven R. Cunningham; Luke Gardner; Maxime M. Grand; Jessica Metter; Ava Salmi; Evan Simpson; Michael Graham; Scott L. Hamilton; Michael R. Schuppenhauer; Daniel J. Gossard (Journal of Applied Phycology, 2025)

Parental perspectives on the use of tumor molecular profiling and germline genetic testing during their children's cancer treatment - Marcelo M. Sleiman; Muriel R. Statman; Mary Rose Yockel; Yelena P. Wu; Jada G. Hamilton; Wendy K. Kohlmann; Jennie Vagher; Soren Feola; Luke D. Maese; Jing Chen; Burton Appel; Casey J. Mehrhoff; et al. (Familial Cancer, 2025)

Does a “robot dog” need legs, ears, and tail? A comparative analysis of intention- and emotion-attribution to Miro-E and Unitree Go1 - Gabriella Lakatos; Patrick Holthaus; Pranjal Sharma; Vignesh Velmurugan; Theodora Hamilton-Holbrook; Lewis Riches; Sílvia Moros; Luke Wood (Biologia Futura, 2025)

A Comprehensive Review on Utilizing Human Brain Organoids to Study Neuroinflammation in Neurological Disorders - Adrian Domene Rubio; Luke Hamilton; Mark Bausch; Mengmeng Jin; Ava Papetti; Peng Jiang; Sowmya V. Yelamanchili (Journal of Neuroimmune Pharmacology, 2025)

Evaluating a microalga (Schizochytrium sp.) as an alternative to fish oil in fish-free feeds for sablefish (Anoplopoma fimbria) - Katherine A. Neylan; Ronald B. Johnson; Frederic T. Barrows; David P. Marancik; Scott L. Hamilton; Luke D. Gardner (Aquaculture, 2024)

Lateglacial and Early Holocene palaeoenvironmental change and human activity at Killerby Quarry, North Yorkshire, UK - Samuel M Hudson; Clive Waddington; Ben Pears; Natalie Ellis; Luke Parker; Derek Hamilton; Inger Greve Alsos; Paul Hughes; Antony Brown (Journal of Quaternary Science, 2023)
The hunter‐gatherers that entered the British peninsula after ice‐retreat were exploiting a dynamic, rapidly changing environment. Records of vegetation change and human occupation during the Lateglacial to Early Holocene in northern Britain are more commonly found at upland and cave sites. However, recent research highlights many areas of the Swale–Ure Washlands that preserve extensive environmental sequences in low‐lying ice‐wastage basins, channels and depressions. The Lateglacial–Early Holocene environment of Killerby Quarry, North Yorkshire, is investigated here using a multi‐proxy approach of sedimentary ancient DNA ( seda DNA), pollen, sedimentological (geochemistry and portable optically stimulated luminescence), and rare and well‐preserved archaeology (Lavvu structures and lithics). Results show that the wetland basins and kettleholes were small lakes or ponds in the Lateglacial surrounded by sedge‐fen and birch woodland. A gradual (centennial scale) succession to reed‐swamp and then marsh is seen by the Early Holocene. This environment formed the resource‐scape for hunter‐gatherer transitory settlement in both the Lateglacial (Late Upper Palaeolithic) and Holocene (Early Mesolithic), attracted by the rich communities of pond‐related flora and fauna as well as easy strategic landscape access by way of the River Swale, an arterial route through the landscape connecting the North Sea Basin with the Pennine uplands via the palaeolakes around Killerby.

Maximizing nutrient recovery from aquaponics wastewater with autotrophic or heterotrophic management strategies - Peng Chen; Hye-Ji Kim; Luke Raymond Thatcher; Joshua Michael Hamilton; Makayla L. Alva; Zhi Zhou; Paul B. Brown (Bioresource Technology Reports, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Dietary intake, eating behavior and physical activity in individuals with and without obstructive sleep apnea - Caroline J. Beatty; Shane A. Landry; Joy Lee; Simon A. Joosten; Anthony Turton; Denise M. O’Driscoll; Ai-Ming Wong; Luke Thomson; Bradley A. Edwards; Garun S. Hamilton (Sleep and Biological Rhythms, 2021)

The capacity of biochar made from common reeds to neutralise pH and remove dissolved metals in acid drainage - Luke M. Mosley; Philip Willson; Benjamin Hamilton; Greg Butler; Russell Seaman (Environmental Science and Pollution Research, 2015)